Long-term influence of cyanobacterial bloom on the immune system of Litopenaeus vannamei. Issue 61 (February 2017) - Gao, Jiefeng; Zuo, Hongliang; Yang, Linwei; He, Jian-Hui; Niu, Shengwen; Weng, Shaoping; He, Jianguo; Xu, Xiaopeng
Abstract: Cyanobacteria are ubiquitously distributed in water on the Earth. It has long been known that the cyanobacterial bloom in aquaculture ponds can cause acute and massive deaths of shrimp. However, the long-term and chronic effects of the cyanobacterial bloom on shrimp are still poorly understood. In this study, the immune state of white pacific shrimp, Litopenaeus vannamei, surviving a naturally occurring cyanobacterial bloom was investigated and tracked for 70 d. Compared with the control, the growth of shrimp suffering high concentrations of cyanobacteria was obviously postponed. In these shrimp, the activities of the NF-κB, JAK/STAT and P38 MAPK immune signaling pathways and the expression of many antimicrobial peptide genes were down-regulated, whereas the expression of C-type lectins was significantly up-regulated. Although the mRNA level of lysozyme was reduced, the expression of the invertebrate-type lysozyme gene was increased. Furthermore, the concentration of hemocytes in hemolymph was greatly decreased, but the phagocytic activity of hemocytes was increased. These suggested that the cyanobacterial bloom has significant and complex influences on the immune system of shrimp, and in turn, alteration of the immune state could be a factor by which few shrimp can survive the cyanobacterial bloom. Thus, the current study could help further understand the interactions between the aquaculture water environment and the immune system of shrimp. Highlights: The immune state of shrimp living in cyanobacterial bloom water was investigated. The NF-κB, JAK-STAT and P38 MAPK pathways were suppressed in shrimp under cyanobacterial stress. Expression of many antimicrobial peptides and lysozyme was down-regulated. Expression of C-type lectins and the invertebrate-type lysozyme was up-regulated. The concentration of hemocytes was reduced, but their phagocytic activity was increased.